Performance Analysis of V2X Services in 5G Millimeter Wave Communication - Gharti, Min Prasad; Joshi, Shashidhar Ram (Journal of Science and Technology, 2023)
Vehicle to everything (V2X) is the connection of vehicle and any other thing like vehicle, infrastructure, network, pedestrian etc. The emerging fifth generation (5G) cellular technology is the key enabler of digitalization of the transportation system which is still not commercialized. Millimeter band radio waves are proposed for 5G technology to get the large bandwidth. The millimeter band radio waves are highly attenuated by rain, vegetation, street lamps, buildings, etc. The emerging application in the field of vehicular industry like high density vehicle platooning, pre-crash sensing and automated overtake requires better quality of service (QoS). The results show the minimum SINR value of LoS channel is -13 dB and minimum SINR value of NLoS is -25.68 dB over the variation of distance from 10m to 400m, where the threshold SINR value is -10dB. The minimum transport block loss in the physical layer is 20% in 5 nodes whereas 60% in 40 nodes with constant distance 150m between gNB and UE in the NLoS channel. The maximum delay found is less than 1.5 millisecond. The Friis propagation loss model is used in the LoS channel whereas the millimeter wave propagation loss as well as the shadowing model is used in the NLoS channel. This research work is validated in NS3 simulator.